Design of Vetiver Handicraft Products, According to the King’s Philosophy, towards Sustainable Development, Case Study: Vetiver Handicraft Products, Ban Pong Samit, Mae Wang District, Chiang Mai Province - Kitipattanawit, Jetsadapol (Community and Social Development Journal, 2024)
This research aimed to 1) study vetiver products in the recent market 2) design and develop vetiver products 3) evaluate opinions on the new designed vetiver products. The representative sample was 100 people from Ban Pong Samit community group. The research persuaded members in the community group to 1. express their opinions for new designed vetiver products 2. join the wickerwork’s knowledge development training. 3. be in the process of promoting vetiver cultivation and own vetiver products creation project. In the beginning, the research found that the community has never used vetivers for weaving or creating products, but had used bamboo stripes for basketry work. Therefore, they were introduced to the training process on how to use vetiver as wicker material. Among the process, the lecturer saw the demands for many kinds of product such as key chains, baskets, doormats, and tissue boxes which were easy to get start. Moreover, according to the community’s context, Ban Pong Samit is an agricultural community where cultivates flowers, rice, and strawberries so they chose strawberry as identity of their community’s vetiver products. After designing and development, the result shown satisfaction opinions levels as follow: in terms of design, the satisfaction score was 4.51 (a very good level), in terms of the suitability for the area, the satisfaction score was 4.61 (a very good level), and in term of using local material and able to support weight by still conveying the local wisdom, the satisfaction score was 4.56, also in a very good level.